Effects of nitrogen deposition on soil sulfur cycling. Issue 11 (2nd November 2016) - Chen, Hao; Yang, Liqiong; Wen, Li; Luo, Pan; Liu, Lu; Yang, Yi; Wang, Kelin; Li, Dejun
Abstract: Increased atmospheric nitrogen (N) deposition has been found to alter processes and functions of terrestrial ecosystems including the biogeochemical cycling of N and other elements, e.g., phosphorus (P), calcium (Ca), and potassium (K). Nevertheless, how N deposition changes sulfur (S) cycling is largely unknown. Based on a meta‐analysis and a lab N addition experiment, here we show that N addition significantly suppresses the activity of soil arylsulfatase, which is a major enzyme involved in the mineralization of organic S. The evidence suggests that N‐induced decrease in soil pH is responsible for the decrease of arylsulfatase activity. Soil buffering capacity plays a critical role in mediating the extent of arylsulfatase activity response to N inputs via its regulation on soil pH. Our results suggest that N deposition may slow down S cycling by suppressing soil organic S mineralization. Key Points: Effects of N deposition on S cycling were addressed using meta‐analysis and incubation experiment N inputs slow down S cycling by suppressing soil arylsulfatase activity Soil buffering capacity mediates the response extent of arylsulfatase to N inputs